2011
DOI: 10.1016/j.adolescence.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in youths’ political engagement and participation. The role of parents and of adolescents’ social and civic participation

Abstract: Research examining youths' political development mostly focused on young people as a general group; comparatively less attention has been devoted to the examination of gender pathways toward citizenship. Two studies were conducted addressing (a) the role of parents' participation and the moderating role of adolescent gender and age group (n = 1419) and (b) the role of adolescent social and civic participation and the moderating role of adolescent gender and type of school (n = 1871). Results confirmed the gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 46 publications
11
121
1
7
Order By: Relevance
“…The Internet in this sense can be an opportunity but also a trap, if people do not move from the virtual to the real public life domain. Gordon (2008) emphasised the need to increase females' opportunities to emerge as political actors; Cicognani et al (2012) underlined the influential role of mothers. We propose reconsidering the family as a catalyst for participation, in order to increase female manifest political participation and to reduce the gender gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Internet in this sense can be an opportunity but also a trap, if people do not move from the virtual to the real public life domain. Gordon (2008) emphasised the need to increase females' opportunities to emerge as political actors; Cicognani et al (2012) underlined the influential role of mothers. We propose reconsidering the family as a catalyst for participation, in order to increase female manifest political participation and to reduce the gender gap.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising: there is a huge amount of research that has shown that young people follow their parents' political orientations (McFarland & Thomaswith, 2006), even if few studies suggest specific gender effects. Cicognani et al (2012) found a more influential role of mothers compared to fathers, while Matthews, Hempel and Howell (2010) found that family education was more influential in predicting civic participation for girls than for boys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, considering the gender differences highlighted in the literature on civic engagement (with females generally scoring higher in civic engagement and voluntary behavior: e.g., Cicognani et al 2012), we used a multiple group model to test, without any specific hypotheses, the extent to which the proposed theoretical model is consistent across gender.…”
Section: The Proposed Conceptual Modelmentioning
confidence: 99%
“…It may include a number of dimensions, but overall, civic engagement is a "process in which people take collective action to address issues of public concern" (Checkoway & Aldana, 2013, p. 1894) and "promot[e] the quality of life in a community" (Ehrlich, 2000, p. 4). Thus, through both political participation, such as demonstrations, boycotts, strikes, or signing a petition (Cicognani, Zani, Fournier, Gavray, & Born, 2012), and non-political processes, such as volunteering, community service, sports or recreational clubs, cultural associations (Bringle, 2005;Cicognani et al, 2012), youth may try to improve their social environments. These two forms of civic engagement, political participation and volunteering, are not entirely interconnected nor entirely separate constructs; in fact, social participation such as volunteering often paves the way for political participation (Gauthier, 2003).…”
Section: Civic Engagementmentioning
confidence: 99%